FACTORS INFLUENCING THE PERFORMANCE OF TRAWL OPERATION IN THE WATERS AREA OF TARAKAN - Asep Priatna; Suprapto Suprapto (Research Center for Fisheries, 2017)
Any fish on swept area of bottom trawl could not be caught due to some technical factors during towing. However, it could be estimated by integrated of bottom trawl and acoustic survey. This paper describes the determination of some factors that affect the performance of trawl net during the bottom trawl survey in the waters of Tarakan. Surveys were carried out in May, August, and November 2012. A total of 57 stations of simultaneously acoustic-trawl were completed. Data collected from each station include catch composition, and variables of trawling operation (i.e. bottom depth, warp length, trawl door opening, towing speed, towing duration, and acoustic fish density). Principal component analysis was applied to identify variables might impact of trawling performance (i.e. fish density at the waters area, towing speed, towing duration, warp length, horizontal opening of trawl door, density of non-demersal at cod end, and bottom depth). Both towing speed and towing duration were not major component for trawl operation. According to test of significance for four variables (i.e. bottom depth, warp length, horizontal opening, biota non-demersal at cod end) which affected to fish density at waters area, that both of variable (i.e. warp length and bottom depth) were significant as the principal components for the performance of bottom trawl.